Działalność wydawnicza Kanadyjsko – Polskiego Instytutu Badawczego w Toronto (1956-2016) - Gliński, Waldemar (Saeculum Christianum. Pismo Historyczne, 2019)
The Canadian-Polish Research Institute was founded in 1956 by Wiktor Turek, who was also its first president. The following presidents of the Institute were: Tadeusz Krychowski (1963-1972), Rudolf K. Kogler (1972-1995), Edward Sołtys (1995-2011), and Joanna Lustański (from 2011). During the sixty years of its existence, the Institute published about 50 books. There are several dominant thematic profiles among them: 1. bibliographic books (Polonica Canadiana, The Polish Language Press in Canada); 2. registers of Polish scientists and a list of Polish artists, writers and musicians; 3. memories; 4. monographs on the history of Polish settlement in Canada, as well as Polish institutions and organizations; 5. other publications: an English translation of Melchior Wańkowicz's Three Generations, a volume of poetry and prose by Danuta Bieńkowska – Beetwen the Shores, a monograph on the sciences of law by prof. Tadeusz Grygier Sprawiedliwość, czyli istota moralności, zdrowia i prawa, and the book of Edward Sołtys Black Ribbon Day. The publishing achievements of the Canadian-Polish Research Institute are of paramount importance for promoting the contribution of Poles living in Canada. This participation includes the activity of Polish engineers, scientists, artists, clerics, veterans, social and political activists. Their presentation in the form of studies issued by the Institute is an important element of the Polish public and historical diplomacy.